Mapping internal knowledge transfers in multinational corporations - Rita Castro; António Carrizo Moreira (Administrative Sciences, 2023)
Managing multiple knowledge transfers between headquarters and subsidiaries, among subsidiaries, and also within each of these units is crucial for multinational corporations' (MNCs) survival. Therefore, this article aims to uncover the main factors influencing internal knowledge transfers in MNCs-including intra-unit knowledge transfers and transfers between units, namely, conventional, horizontal, and reverse knowledge transfers. To achieve this goal, a systematic literature review (SLR) was conducted to synthesize the content of 85 articles. From a set of 1439 papers, only 85 related to knowledge transfer and knowledge sharing were considered. Based on an inductive thematic approach, eight different research categories and 97 topics were identified. Four different internal knowledge transfers (intra knowledge transfer (IKT), horizontal knowledge transfer (HKT), conventional knowledge transfer (CKT), and reverse knowledge transfer (RKT)) are compared across eight thematic categories and 97 topics. According to the results obtained, the depth of the topics analyzed varies, as does the variety of categories, with RKT being more deeply analyzed than IKT. There is a clear dominance of vertical knowledge transfer (CKT + RHT) over HKT. The exercise of power (e.g., size, knowledge base) still dominates CKT and RKT in most of the studies analyzed, which are traditionally affected by the characteristics of MNCs, HQs and subsidiaries. The debate on HKT is affected by the classical perspectives of power-based relations (e.g., expatriates, size, knowledge base) among subsidiaries. Although important, intra-unit knowledge transfer is greatly influenced by characteristics.
Keywords: 350; conventional knowledge transfer; horizontal knowledge transfer; internal knowledge; intra-unit knowledge transfer; knowledge management; knowledge transfer; multinational corporations; reverse knowledge transfer; systematic literature review